Ice collapse over trapped water bodies on Enceladus and Europa. Issue 3 (3rd February 2015) - Walker, C. C.; Schmidt, B. E.
Abstract: Icy satellite surfaces are riddled with geological indicators that can inform what lies beneath. Here we investigate effects of trapped or perched subsurface liquid water on the surface above. We use two models to investigate these effects: first, an analytical model to determine the flexural response of an ice shell to the existence of trapped water, and second, a discrete element model that simulates collapse of ice through granular interactions to determine possible topography that would result from this stress being placed on the ice. We find that for Europa's likely trapped water pockets below chaos terrains and a localized sea below Enceladus' South Polar Terrain, these models can reproduce observed geology of both features. Thus, we postulate that it is likely that Europa's chaos terrains and Enceladus' South Polar Terrain formed due to a similar mechanism: ice collapse above trapped water. Key Points: Formation of a subsurface trapped water body affects ice surface topography Ice lid collapses, forms different surface features depending on water geometry Trapped water formed Europa's chaos terrain and Enceladus' South Pole Terrain